2015
DOI: 10.1152/ajplung.00309.2014
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary epithelial barrier function: some new players and mechanisms

Abstract: The pulmonary epithelium serves as a barrier to prevent access of the inspired luminal contents to the subepithelium. In addition, the epithelium dictates the initial responses of the lung to both infectious and noninfectious stimuli. One mechanism by which the epithelium does this is by coordinating transport of diffusible molecules across the epithelial barrier, both through the cell and between cells. In this review, we will discuss a few emerging paradigms of permeability changes through altered ion transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
134
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(141 citation statements)
references
References 209 publications
(1 reference statement)
1
134
0
6
Order By: Relevance
“…Epithelial cell-cell junctions bind epithelial cells into the cohesive barrier between the lumen of the epithelium and the parenchyma. Respiratory epithelial junctions have been extensively reviewed elsewhere (193)(194)(195). This section serves to summarize their function and relevance in the maintenance of epithelial barrier function and host tolerance to pulmonary infection.…”
Section: Modulation Of Respiratory Epithelial Barrier Dynamicsmentioning
confidence: 99%
“…Epithelial cell-cell junctions bind epithelial cells into the cohesive barrier between the lumen of the epithelium and the parenchyma. Respiratory epithelial junctions have been extensively reviewed elsewhere (193)(194)(195). This section serves to summarize their function and relevance in the maintenance of epithelial barrier function and host tolerance to pulmonary infection.…”
Section: Modulation Of Respiratory Epithelial Barrier Dynamicsmentioning
confidence: 99%
“…A recent study reported that TREK-1 deficiency in TREK-1 KO mice resulted in increased lung damage (23). The authors proposed that the deficiency could have an impact on cytokine secretion and epithelial barrier function, and that the dysregulation of these proteins can contribute to the pathogenesis of epithelial injury.…”
Section: Trek-1 In Hirschsprung's Diseasementioning
confidence: 99%
“…; Brune et al . ). Apical K + secretion mediated by BK also increases and sustains Cl − efflux following purinergic receptor stimulation and provides additional solute to increase the osmotic gradient necessary for airway hydration.…”
Section: Introductionmentioning
confidence: 97%
“…The reduced depth of the periciliary fluid layer decreased ciliary beat frequency, which could be fully restored by the addition of apical fluid. An important consequence of reduced ciliary beating and ASL volume is impaired mucus clearance, which is observed in certain airway diseases including CF, asthma and COPD (Jansen et al 1995;Livraghi & Randell, 2007;Bhowmik et al 2009;Boon et al 2014;Brune et al 2015). Apical K + secretion mediated by BK also increases and sustains Cl − efflux following purinergic receptor stimulation and provides additional solute to increase the osmotic gradient necessary for airway hydration.…”
Section: Introductionmentioning
confidence: 99%